Digital signal processing laboratory using MATLAB Sanjit K. Kumar - Mitra, Sanjit Kumar (WCB/McGraw Hill, 1999)
Intended for a computer-based DSP laboratory course that supplements a lecture course on Digital Signal Processing. This book includes 11 laboratory exercises. It teaches the reader, through tested programs in the first half of the book. In the second half of the book, the student is asked to write MATLAB programs to carry out the projects.